Pengaruh Kinerja Lingkungan Dan Biaya Lingkungan Terhadap Kinerja Keuangan - Rizka Annisya Putri Latifah; nikmah (JURNAL FAIRNESS, 2021)
This study aims to provide empirical evidence of the effect of environmental performance and environmental costs on financial performance. This study was tested using multiple regression analysis. The sample used in the study was BUMN companies that are going public and not going public in 2012- 2018 with a total sample of 77 observations.The results of this study indicate that environmental performance has a significant positive effect on financial performance. Meanwhile, environmental costs do not have a significant effect on financial performance and firm size has a negative effect on financial performance